2014
DOI: 10.1080/09603107.2014.925054
|View full text |Cite
|
Sign up to set email alerts
|

Volatility transmission across currencies and stock markets: GIIPS in crisis

Abstract: This article explores the structure of the volatility transmission mechanism between stock and currency markets for Eurozone economies with systemic fiscal problems such as Greece, Italy, Ireland, Portugal and Spain. We focus on the structural properties of volatility diffusion, in times of market instability, illiquidity, fiscal crisis as well as political uneasiness. Our evidence indicates the presence of bidirectional, asymmetric volatility spillovers between currency and stock markets. Our empirical findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…They reported that news shocks in the Japanese currency market account for volatility transmission in eight out of ten industrial sectors in Japan. Andrikopoulos et al (2014) explored the volatility transmission mechanism between stock and currency markets for Eurozone economies, such as Greece, Italy, Ireland, Portugal and Spain. They found a bidirectional, asymmetric volatility spillover effect between currency and stock markets in these countries.…”
Section: Literature Review and Related Studiesmentioning
confidence: 99%
“…They reported that news shocks in the Japanese currency market account for volatility transmission in eight out of ten industrial sectors in Japan. Andrikopoulos et al (2014) explored the volatility transmission mechanism between stock and currency markets for Eurozone economies, such as Greece, Italy, Ireland, Portugal and Spain. They found a bidirectional, asymmetric volatility spillover effect between currency and stock markets in these countries.…”
Section: Literature Review and Related Studiesmentioning
confidence: 99%
“…Similarly, investors in other equities and currency markets of the world were found to be more risk-averse due to the shock in the US equity markets (Beirne and Gieck, 2014). In another study, Andrikopoulos et al (2014) found evidence of bidirectional asymmetric volatility transmission between the exchange and stock markets in European economies. Although these studies provide significant evidence of cross-asset market linkages, the majority of these studies focus on developed countries and pay less attention to emerging ones, such as BRICS countries.…”
Section: Volatility Spillovermentioning
confidence: 91%
“…The findings obtained from the analysis concluded that while no long-term relationship between variables was found, negative fluctuations in the exchange rate caused a decrease in stock prices. Some studies reveal the relationship between stocks (stock exchanges) and exchange rates in samples of various countries, regions and economies using their volatility spillover (See O'Donnell & Morales 2009; Lee et al 2011;Walid et al 2011;Andrikopoulos et al 2014;Sui and Sun 2016;Sikhosana and Aye 2018;, Akdağ and Yıldırım 2019;Şenol 2020;Ozdemir 2020;Maura and Trebelsi 2020;Baranidharan and Alex 2020). O'Donnell and Morales (2009) analyzed the volatility spillover between exchange rates and stocks in the Czech Republic, Hungary, Poland, and Slovakia sample.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study results showed that the relationship between stocks and exchange rate markets depends on their regime, and the volatility in stocks responds asymmetrically to the events in the exchange rate markets. Andrikopoulos et al (2014) examined the volatility spillover between stocks and exchange rates in a sample of countries experiencing foreign debt crises and financial problems in the Eurozone.…”
Section: Literature Reviewmentioning
confidence: 99%